Indoreonectes mahadeoensis, a new species of river loach from headwaters of the Narmada River, India (Teleostei: Nemacheilidae) - Ghosh, Meghma; Bhat, Anuradha; Johnson, Jeyaraj Antony (Zootaxa, 2025)
A new species of nemacheilid loach, Indoreonectes mahadeoensis is described from the Narmada River basin, Central India. Indoreonectes mahadeoensis is distinguished from its congeners by the presence of 8 branched rays in the dorsal fin, 7 branched rays in the anal fin, and by the unique combination of the following characters: nasal barbels reaching anterior border of eye, dorsal-fin origin positioned posterior to vertical line drawn from pelvic-fin origin, and broken bars along lateral surface of body. Further, I. mahadeoensis differs from all congeners, except I. evezardi, in having divided vertical bars on caudal peduncle (vs. undivided bars), but can be distinguished from the latter in having larger eyes (16.5–21.8 vs. 9.8–15.9% HL) and wider gape (40.4–59.1 vs. 24.3–37.5% HL). Analysis of the mitochondrial cytochrome b gene sequences revealed high genetic divergence (uncorrected P-distance ranging from 11.2 to 18.6%) between I. mahadeoensis and congeners.